Simulation and modeling methodologies, Technologies and applications : 7th International Conference, SIMULTECH 2017 Madrid, Spain, July 26-28, 2017 revised selected papers /: 7th International Conference, SIMULTECH 2017 Madrid, Spain, July 26-28, 2017 revised selected papers. ([2019]) - Unknown
No abstract available